The genesis and development of the Angolan political and administrative system from 1975 to the present - Vidal, Nuno (2014)
This paper discusses the development of the Angolan political-administrative system since the independence, not so much in terms of its inner working logic which I called post-modern in a recently published work , but focusing in one of its specific processes, namely the concentration of political power and administrative centralization paralleled by an increasing 'elitism' in the access to patrimonial benefits and privileges. Such type of processes are common to many other political systems of patrimonial character in sub-Saharan Africa, however, contrary to what is usually referred as the common path, the Angolan case did not reach a point of operative stabilisation but continued unabated towards an extreme. Constructed over two presidential administrations (since the independence) and having survived the end of the Socialist model, such distinctiveness of Angolan patrimonialism runs the risk of perpetuating itself in the supposedly 'new era' of multiparty democracy. This paper is divided in three parts, the first gives a brief analytical framework, the second and the third deal with the administration of Agostinho Neto and Eduardo dos Santos respectively.